Large‐Area Synthesis of Ultrathin, Flexible, and Transparent Conductive Metal–Organic Framework Thin Films via a Microfluidic‐Based Solution Shearing Process. Issue 12 (10th February 2022) - Lee, Taehoon; Kim, Jin‐Oh; Park, Chungseong; Kim, Hanul; Kim, Min; Park, Hyunmin; Kim, Ikjin; Ko, Jaehyun; Pak, Kyusoon; Choi, Siyoung Q.; Kim, Il‐Doo; Park, Steve
Abstract: Iminosemiquinone‐linker‐based conductive metal–organic frameworks (c‐MOFs) have attracted much attention as next‐generation electronic materials due to their high electrical conductivity combined with high porosity. However, the utility of such c‐MOFs in high‐performance devices has been limited to date by the lack of high‐quality MOF thin‐film processing. Herein, a technique known as the microfluidic‐assisted solution shearing combined with post‐synthetic rapid crystallization (MASS‐PRC) process is introduced to generate a high‐quality, flexible, and transparent thin‐film of Ni3 (hexaiminotriphenylene)2 (Ni3 (HITP)2 ) uniformly over a large‐area in a high‐throughput manner with thickness controllability down to tens of nanometers. The MASS‐PRC process utilizes: 1) a micromixer‐embedded blade to simultaneously mix and continuously supply the metal–ligand solution toward the drying front during solution shearing to generate an amorphous thin‐film, followed by: 2) immersion in amine solution for rapid directional crystal growth. The as‐synthesized c‐MOF film has transparency of up to 88.8% and conductivity as high as 37.1 S cm −1 . The high uniformity in conductivity is confirmed over a 3500 mm 2 area with an arithmetic mean roughness ( R a ) of 4.78 nm. The flexible thin‐film demonstrates the highest level of transparency for Ni3 (HITP)2 and the highest hydrogen sulfide (H2 S) sensing performance (2, 085% at 5 ppm) among c‐MOFs‐based H2 S sensors, enabling wearable gas‐sensing applications. Abstract : A microfluidic‐assisted solution shearing combined with post‐synthetic rapid crystallization (MASS‐PRC) process is introduced, which enables the formation of high‐quality conductive Ni3 (HITP)2 thin‐films with thickness controllability down to 10 nm in a rapid large‐area scalable manner. This process can fabricate flexible and transparent Ni3 (HITP)2 thin film for high‐performance wearable gas sensors.